Penerapan Sistem Informasi dan Jaringan Komputer dalam Literasi Digital Siswa SMP MA`ARIF NU 1 Purwokerto - Dinda Isna Nur Laeli; Niessye Hani Wijaya; Muhammad Izzedien Pratama; Nur Muhamad Dwi Jayanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The rapid advancement of information technology demands that the younger generation possess adequate digital literacy from an early age. This study aims to evaluate the effectiveness of a community service activity focused on educating junior high school students at SMP Ma’arif NU 1 Purwokerto about computer systems and computer networks. The research employed a descriptive qualitative approach with data collection techniques including observation, semi-structured interviews, documentation, as well as pre-tests and post-tests. The activity involved students from classes 9A, 9B, and 9C, who participated in interactive learning sessions covering basic materials on computer systems, computer networks, and digital safety. The results indicate an increase in students' understanding of information technology concepts, as reflected by improved comprehension scores and positive responses toward the program. Students demonstrated high enthusiasm, actively engaged in discussions, and were able to explain the material presented. These findings suggest that an educational approach based on hands-on practice is effective in enhancing digital literacy among students. The implication of this activity highlights the importance of continuous technology education at the basic education level to prepare the younger generation for the challenges of the digital era and to encourage their active contribution to a technology-based society.